1999
DOI: 10.1016/s0022-2275(20)32462-7
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor BI (SR-BI) mediates free cholesterol flux independently of HDL tethering to the cell surface

Abstract: In addition to its effect on high density lipoprotein (HDL) cholesteryl ester (CE) uptake, scavenger receptor BI (SR-BI) was recently reported to stimulate free cholesterol (FC) flux from Chinese hamster ovary (CHO) cells stably expressing mouse SR-BI, a novel function of SR-BI that may play a role in cholesterol removal from the vessel wall where the receptor can be found. It is possible that SR-BI stimulates flux simply by tethering acceptor HDL particles in close apposition to the cell surface thereby facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(75 citation statements)
references
References 28 publications
7
66
0
2
Order By: Relevance
“…onstrated that the expression of SR-BI stimulates both the efflux of cell cholesterol and influx of HDL cholesterol (Table 2); thus, SR-BI creates an environment in which the bi-directional flux of FC is increased (80). However, the expression of SR-BI does not increase the efflux of cell cholesterol to lipid-free apoA-I, even though the apolipoprotein is bound to the receptor (79,80). Thus, the efflux of cholesterol to lipid-free apolipoproteins and the efflux to phospholipid-containing acceptors are two independent processes.…”
Section: Observation 7: the Rate Of Cell Cholesterol Release And The Extent Of Stimulation By Phospholipid Supplementation Of Serum Corrementioning
confidence: 99%
See 1 more Smart Citation
“…onstrated that the expression of SR-BI stimulates both the efflux of cell cholesterol and influx of HDL cholesterol (Table 2); thus, SR-BI creates an environment in which the bi-directional flux of FC is increased (80). However, the expression of SR-BI does not increase the efflux of cell cholesterol to lipid-free apoA-I, even though the apolipoprotein is bound to the receptor (79,80). Thus, the efflux of cholesterol to lipid-free apolipoproteins and the efflux to phospholipid-containing acceptors are two independent processes.…”
Section: Observation 7: the Rate Of Cell Cholesterol Release And The Extent Of Stimulation By Phospholipid Supplementation Of Serum Corrementioning
confidence: 99%
“…In addition, the ability of PL supplementation of serum or HDL to enhance the rate of cholesterol efflux is also improved by SR-BI expression. This increase in cholesterol flux is not entirely accomplished by the tethering of the acceptor particle to the membrane, but rather it is largely due to changes in the organization of the lipids in the plasma membrane (80). Because at least some of the SR-BI tends to locate in caveolae (78,90) it is likely that the SR-BI-induced changes in plasma membrane organization involve caveolae and/or lipid rafts (84,91).…”
Section: Mechanism 1: Desorption Of Cholesterol Molecules Out Of the Plasma Membrane And Diffusion Through The Aqueous Phase To Phospholimentioning
confidence: 99%
“…However, the contribution of SR-BI in peritoneal macrophages may be limited, as message levels for CD36 are far more abundant (12). Although its efficiency is 7-fold less than SR-BI, CD36 can also facilitate the selective uptake of HDL cholesterol (31), suggesting that the down-Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that although HDL binding to CD36 is greater than its binding to SR-BI, only the latter promoted significant cholesterol efflux. Moreover, there was more cholesterol efflux to phospholipid vesicles (which do not bind to surface receptors) in SR-BI-expressing cells than in CD36-expressing cells (27). These results led to the conclusion that SR-BI promotes cholesterol efflux through a process not dependent on the tethering of HDL to its receptor (27).…”
Section: Sr-bimentioning
confidence: 97%
“…There is some controversy surrounding the question of whether HDL must physically bind to SR-BI in order to mediate cholesterol efflux. Rothblat and co-workers (27) compared HDL binding to SR-BI and to another scavenger receptor, CD36. They showed that although HDL binding to CD36 is greater than its binding to SR-BI, only the latter promoted significant cholesterol efflux.…”
Section: Sr-bimentioning
confidence: 99%